ANALYSIS OF APO-B SERUM LEVELS IN BALB/C MICE HYPERCHOLESTEROLEMIC AGAINST TEMULAWAK EXTRACT (Curcuma xanthoriza Roxb) - Riyadatus Solihah; M. Shofwan Haris; Yogi Khoirul Abror (Universitas Nahdlatul Ulama Surabaya, 2019)
APO–B Serum levels is the most predictive value for the incidence of atherosclerosis and coronary heart disease. Curcuma xanthorrhiza Roxb contains curcumin, which can be used as an antioxidant, anti–inflammatory and antihypercholesterol. The mechanism of curcumin contained in ginger to reduce cholesterol is due to its function as a cholagoga or bile stimulant. This study aims to determine the effect of temulawak extract on the levels of APO–B Serum in hypercholesterolemia mice. This research were a true experimental study with a post–test only control group design carried out in February 2018. The extraction As much as 25 mice were divided into 5 groups where are group consisted of 5 mice. Positive control group (K+) were treated with high cholesterol feed and water, negative control group (K–) were given standard feed and water, treatment group 1 (P1) were given high cholesterol food and 25mg/kg BW of curcuma extract for 14 days, treatment group 2 (P2) were treated with foods high in cholesterol and 50mg/kg BW of curcuma extract for 14 days and treatment group 3 (P3) treated with high cholesterol and ginger extract 75mg/kg BW for 14 days. Examination of APO–B levels were measured using the spectrophotometric method. Data were analyzed using One–Way Anova. The results showed that the average of APO–B level at (K+) was 209.7 ± 1.02 mg / dL, at (K–) 115.3 ± 1.04 mg / dL, at (P1) 180.4 ± 1.07 mg / dL, at (P2) 147.6 ± 1.12 mg / dL, at (P3) 119.1 ± 1.10 mg / dL. Based on the results of statistical test it was found that there was a significant decrease in APO–B levels with p–value= 0.001 at alpha 0.05 (p <α).